Characteristics and Performance Assessment of Approaches Pre-rendering and Isomorphic Javascript as a Complement to SPA Architecture - Silva, William Oliveira da; Farah, Paulo Roberto (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS), 2018)
The SPA (Single Page Application) architecture is very popular these days because of its advantages over traditional multi-page web architecture. Mainly because of its more fluid page navigation experience. However, SPAs have the disadvantage of a longer page load that can be critical in some cases. This work aimed to study and compare the approaches of prerendering and isomorphic JavaScript as a complement to the SPA architecture in order to mitigate the observed disadvantage. These approaches were analyzed on two different aspects: page load performance and server resources utilization. The results show that isomorphic JavaScript approach is able to present the complete page in up to 47% before the time SPA finish and the speed index metric demonstrate that isomorphic architecture has a visual progress 48% faster than SPA. However, isomorphic architecture throughput reached only 20 requests/s and SPA served more than 700 requests/s, while prerendering approach achieved only 1 request/s.